2017
DOI: 10.1021/acs.orglett.7b02329
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Ralsolamycin, the Interkingdom Morphogen from the Crop Plant Pathogen Ralstonia solanacearum

Abstract: Ralsolamycin, an inducer of chlamydospore formation in fungi, was recently reported from the plant pathogenic bacterium Ralstonia solanacearum. Although interpretation of tandem mass data and bioinformatics enabled a preliminary chemical characterization, the full structure of ralsolamycin was not resolved. We now report the recovery of this secondary metabolite from an engineered R. solanacearum strain. The structure of ralsolamycin was elucidated by extensive spectroscopic analyses. Chemical derivatization a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 32 publications
1
39
1
Order By: Relevance
“…A previous study showed that R. solanacearum produces ralsolamycin to induce chlamydospore formation in fungi [ 24 ]. As both R. solanacearum and S. scitamineum are plant pathogens, we investigated whether competition exists between the two pathogens.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous study showed that R. solanacearum produces ralsolamycin to induce chlamydospore formation in fungi [ 24 ]. As both R. solanacearum and S. scitamineum are plant pathogens, we investigated whether competition exists between the two pathogens.…”
Section: Resultsmentioning
confidence: 99%
“…1 , 3 ). Some previous studies have also revealed that R. solanacearum employs QS to control the production of ralsolamycin to achieve a fitness advantage in inter-kingdom competition [ 24 26 ]. Our new findings suggested that complicated mechanisms have evolved in R. solanacearum to achieve for a competitive advantage in the microbial community.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The chromosome encodes a complete gene cluster for micacocidin biosynthesis, a siderophore utilizing a hybrid pathway of nonribosomal peptide synthetase, and a type I iterative polyketide synthase ( 11 ). The megaplasmid encodes genes involved in the production of the antibiotic lipopeptide ralstonin/ralsolamycin, with established phytotoxic ( 12 , 13 ) and antifungal ( 12 , 14 ) activities, and a putative bacteriocin. Biosynthetic gene clusters for exopolysaccharide, terpene, and homoserine lactone production were detected.…”
Section: Announcementmentioning
confidence: 99%
“…Although R. solanacearum has been studied primarily because of its severe impacts on plant hosts, it has recently been shown to impact plant-prokaryote community composition ( 5 ), and it also interacts intimately with many soil fungi through volatile and diffusible signaling ( 6 8 ). The lipopeptide ralsolamycin (synonym ralstonin A), produced by a hybrid polyketide synthase/nonribosomal peptide synthetase (PKS-NRPS) biosynthetic gene cluster ( rmy ) ( 7 , 9 , 10 ), was shown to induce chlamydospore formation in a phylogenetically diverse panel of plant-associated and/or soil-inhabiting fungi representing members of the Mucoromycota, Ascomycota, and Basidiomycota ( 7 ). Among the assayed fungi were members of the genus Fusarium .…”
Section: Introductionmentioning
confidence: 99%